Galactic Orbits of Globular Clusters in a Barred Galaxy - Edmundo Moreno (Revista Mexicana de Astronomía y Astrofísica, 2006)
We study the effect of a bar in the galactic orbits of forty-five globular clusters whose absolute proper motions are known. The orbital characteristics of the orbits are compared with those obtained for the case of an axisymmetric galactic potential. Tidal radii are computed and discussed for both cases.